2008
DOI: 10.2209/tdcpublication.49.107
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitory Effect of Cranberry Polyphenol on Cariogenic Bacteria

Abstract: The purpose of this study was to investigate the effect of cranberry polyphenol fraction on mutans streptococci. Hydrophobicity is an important factor in the adherence of bacteria to the tooth surface. We found that cranberry polyphenol fraction significantly decreased the hydrophobicity of Streptococcus sobrinus 6715, Streptococcus mutans MT8148R and JC2 in a dose-dependent manner (pϽ0.05). Biofilm formation by S. sobrinus 6715 and S. mutans MT8148R was inhibited by 100g/ml cranberry polyphenol fraction (pϽ0.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
31
0
3

Year Published

2010
2010
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(36 citation statements)
references
References 16 publications
(4 reference statements)
2
31
0
3
Order By: Relevance
“…Patients with high dental caries scores demonstrated a higher prevalence of hydrophobic bacteria than low caries patients. 66 In addition, compounds that diminish the surface hydrophobicity of S. mutans are now being reported to inhibit bacterial adherence in vitro 6769 and cariogenicity in an animal model. 67 …”
Section: Resultsmentioning
confidence: 99%
“…Patients with high dental caries scores demonstrated a higher prevalence of hydrophobic bacteria than low caries patients. 66 In addition, compounds that diminish the surface hydrophobicity of S. mutans are now being reported to inhibit bacterial adherence in vitro 6769 and cariogenicity in an animal model. 67 …”
Section: Resultsmentioning
confidence: 99%
“…Earlier studies demonstrated a high-molecular-weight mass, nondialyzable material (NDM) prepared from cranberries to contain polyphenolic compounds that inhibited the secretion of proteolytic enzymes by periodontopathogens [9], adhesion of a number of bacterial species [10, 11], and were also shown to interfere with coaggregation of oral bacterial species and biofilm formation by Streptococcus mutans [3, 12]. The polyphenol fraction of cranberry was reported to decrease the hydrophobicity of streptococcal species [12, 13]. …”
Section: Introductionmentioning
confidence: 99%
“…[1819] Weiss and colleagues in 2004 incorporated the NDM fraction of cranberry in a mouth rinse and subjects who used it for 6 weeks reported fewer cariogenic Streptococcus mutans . [20] In yet another study, cranberry fraction demonstrated the deactivation of enzymes glucosyltranferase and fructosyltranferase.…”
Section: Introductionmentioning
confidence: 99%
“…Besides, it also prevented the adhesion of P. gingivalis to various proteins including type I collagen thus reducing bacterial coaggregation in periodontal diseases. [1924]…”
Section: Introductionmentioning
confidence: 99%